1996
DOI: 10.1111/j.1600-0420.1996.tb00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cortical cataractogenesis XVIII. In vitro diabetic cataract reduction by venoruton

Abstract: The effect of a novel flavonoid, venoruton (a mixture of mono-, di-, tri- and tetrahydroxyethylrutosides) has been investigated in healthy rat lenses and compared with diabetic cataract modelled in vitro. One mM venoruton was added to medium simulating healthy and diabetic conditions for the incubated lenses; damage was followed by either stereoscopic photography of the lenses under a Cooperative Cataract Research Group operating microscope or with our recently developed method: the leakage of lactate dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…On the other hand, Vaccinium myrtillus and calcium dobesilate had little effect on the VEGF level despite their antioxidant properties. In addition, Kilic et al [33] reported that the flavonoid preparation Venoruton (a mixture of mono-, di-, tri-and tetrahydroxyethylrutoside), which prevents lens opacification, reduced the level of diabetic cataracts in vitro as a result of its antioxidant effect. However, troxerutin was not effective in preventing cataracts in this study [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Vaccinium myrtillus and calcium dobesilate had little effect on the VEGF level despite their antioxidant properties. In addition, Kilic et al [33] reported that the flavonoid preparation Venoruton (a mixture of mono-, di-, tri-and tetrahydroxyethylrutoside), which prevents lens opacification, reduced the level of diabetic cataracts in vitro as a result of its antioxidant effect. However, troxerutin was not effective in preventing cataracts in this study [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kilic et al [33] reported that the flavonoid preparation Venoruton (a mixture of mono-, di-, tri-and tetrahydroxyethylrutoside), which prevents lens opacification, reduced the level of diabetic cataracts in vitro as a result of its antioxidant effect. However, troxerutin was not effective in preventing cataracts in this study [33]. Also, no dose-effect relationship for troxerutin on body weight and blood glucose was observed in our study or in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, vitamin C, and betacarotene are well-known and effective antioxidants. Novel and new flavanoids, such as venoruton, have also been shown to decrease cataract formation in rat models [Kilic et al, 1996].…”
Section: Exposure Limitsmentioning
confidence: 99%
“…The decrease of antioxidant enzymes mentioned earlier appears to play a pivotal role on the elevation of oxidative stress and cataractogenesis of diabetic cataract [5]. Several lines of evidence have demonstrated that flavonoids, the important phenolic compounds in fruits and vegetables, exert the protective effect against cataractogenesis of diabetic cataract [6, 7]. …”
Section: Introductionmentioning
confidence: 99%